World book 2001. Vol. 21 W-X-Y-Z / Mary Alice Anderson - Anderson, Mary Alice (2001)
united states, the additional eresources, facts in brief, people, way of life, the land, a economy, a important dates wales, questions, wars involving the unirted states, wars of 1812, causes of the war, progress of the war, results of the war, chief battles of the war, kinds of warships, history, Washingto